Mantra Pamaga Diri di Nagari Panti Kabupaten Pasaman - Ayadimal, Dede; Nst., Bakhtaruddin; Nst., M. Ismail (Jurnal Pendidikan Bahasa dan Sastra Indonesia, 2013)
This article was write with the aim of describing the structure of written text Pamagadiri spell, the supporting aspects of Pamaga diri spells and the process of in heriting Pamagadiri spells in Nagari Panti Kecamatan Panti Kabupaten Pasaman. This research uses descriptive method, which is amethod used to describe the state of something objectively. Data were analyzed through the inventory phase, classification, discussion, inference and reporting stage. The results showed that the structur Pamaga diri spells consists of: the opening, the content and the concluding section. Aspects of support mantra are found: (1) the offender,(2)time, (3)events, (4) where, (5) clothes, (6) fixtures, (7) how to bringspell. Process in heritance mantra Pamaga diri consists of two parts: (1) how the acquisition, (2)how in heritance.